2018
DOI: 10.1177/0361198118796359
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Train Drivers’ Cognitive Responses on Rail Accidents

Abstract: Despite the innovations in automatic train control (ATC) systems to reduce the risk of driver error, many rail accidents still occur due to defects in these systems, emphasizing the essential role of the driver in preventing rail accidents and proper control of the train. This paper studies the influence of drivers’ cognitive performance, including attention and visual perception, on the occurrence of rail accidents. The research is conducted using so-called Ex-Post facto method on a random sample of 56 train … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…While some studies suggest that age and train driving performance are unrelated (Edkins & Pollock, 1997; Hani Tabai et al, 2018), Hickey and Collins (2017) found that the train driving performance of older drivers was significantly higher than younger drivers. Also, in the same study, they found that older train drivers had lower working memory than younger drivers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While some studies suggest that age and train driving performance are unrelated (Edkins & Pollock, 1997; Hani Tabai et al, 2018), Hickey and Collins (2017) found that the train driving performance of older drivers was significantly higher than younger drivers. Also, in the same study, they found that older train drivers had lower working memory than younger drivers.…”
Section: Methodsmentioning
confidence: 99%
“…The influence of attentional and cognitive abilities on train driving performance is attracting growing scholarly interest across different rail environments, including light rail, high‐speed rail, and passenger rail services (e.g., Borowsky et al, 2019; Guo et al, 2019; Hani Tabai et al, 2018). In particular, the ability to direct attention to one source of information at a time, known as “selective attention” (Sohlberg & Mateer, 1989), is considered critical to avoid distractions and driving errors (Haga, 1984; Naweed, 2013; Phillips & Sagberg, 2014; Smiley, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation